2019
DOI: 10.1159/000497620
|View full text |Cite
|
Sign up to set email alerts
|

Die Behandlung der sozialen Angststörung und ängstlich-vermeidenden Persönlichkeitsstörung in der Versorgung: eine naturalistische Studie zu einer kombinierten Einzel- und Gruppentherapie

Abstract: Schlüsselwörter Effectiveness • Gruppentherapie • Soziale Phobie • Ängstlich-vermeidende Persönlichkeitsstörung Zusammenfassung Hintergrund: Eine Vielzahl von randomisiert-kontrollierten Studien belegen die Wirksamkeit der kognitiven Verhaltenstherapie (KVT) für soziale Ängste. Die Wirksamkeit der KVT unter Routinebedingungen wurde allerdings seltener untersucht. In den wenigen naturalistischen Studien werden Ergebnisse ausschließlich für die soziale Angststörung (SAS) berichtet. Befunde für die ängstlich-verm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It is noteworthy that effectiveness trials have generally reported a high number of sessions than that reported in RCTs. Boettcher et al (2020) reported an average of 63 sessions, whereas other trials have reported an average number of sessions ranging from 25 to 33 (Crecelius & Hiller, 2014; Gaston et al, 2006; Hoyer et al, 2017; McEvoy, 2007). The longer duration in the effectiveness trials might be required if patients present with a multitude of problems that need a longer time to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that effectiveness trials have generally reported a high number of sessions than that reported in RCTs. Boettcher et al (2020) reported an average of 63 sessions, whereas other trials have reported an average number of sessions ranging from 25 to 33 (Crecelius & Hiller, 2014; Gaston et al, 2006; Hoyer et al, 2017; McEvoy, 2007). The longer duration in the effectiveness trials might be required if patients present with a multitude of problems that need a longer time to be addressed.…”
Section: Discussionmentioning
confidence: 99%